Epidemiology of Perinatal HIV Transmission in the United States in the Era of Its Elimination. Issue 6 (June 2019) - Nesheim, Steven R.; FitzHarris, Lauren F.; Mahle Gray, Kristen; Lampe, Margaret A.
Abstract : The number of infants born with HIV in the United States has decreased for years, approaching the Centers for Disease Control and Prevention's incidence goal for eliminating perinatal HIV transmission. We reviewed recent literature on perinatal HIV transmission in the United States. Among perinatally HIV-exposed infants (whose mothers have HIV, without regard to infants' HIV diagnosis), prenatal and natal antiretroviral use has increased, maternal HIV infection is more frequently diagnosed before pregnancy and breast-feeding is uncommon. In contrast, mothers of infants with HIV are tested at a lower rate for HIV, receive prenatal care less often, receive antiretrovirals (prenatal and natal) less often and breastfeed more often. The incidence of perinatal HIV remains 5 times as high among black than white infants. The annual number of births to women with HIV was estimated last for 2006 (8700) but has likely decreased. The numbers of women of childbearing age living with HIV and HIV diagnoses have decreased. The estimated time from HIV infection to diagnosis remains long among women and men who acquired HIV heterosexually. It is important to review the epidemiology and to continue monitoring outcomes and other health indicators for reproductive age adults living with HIV and their infants.